Rupturas e reconstruções: migração forçada e redes sociais em meio da guerra em Colômbia - Cruz, Olga Del Pilar Vásquez (Universidade Federal de São Carlos, 2007)
The history of Colombia is characterized by violent processes of population expulsion that date back half of the twentieth century and which has been deepened as a consequence of internal armed conflict which resumes in 90´s. Since 1985 until nowadays, 3,700,000 people have been displaced. Who is obliged to flee, leaves rural areas to the cities closest to his place of housing. However, the deepening of the conflict is forcing people continue moving to the big cities, where are greater opportunities for anonymity. Thus, considering the peculiarities of internal displacement, we proposed to characterize -from the perception of actors- the personal networks of a group of migrants by the internal armed conflict, which today live in neighborhoods of Ciudad Bolivar in Bogotá. This is, the way of the networks act, are affected and rebuilt on the migratory path. Our aim was evident if, in the same way as it happens with other types of migration, there is a logic of communication, permanence, re-configuration and organization of social networks; In addition to describe the situations that facilitate, influence or limit these processes. The methodology of research emphasized on record -in a notebook and a record- the comments made by people and the narratives during the contact with the researcher in informal and formal interviews. The configuration of personal networks was complemented with the application of a survey. As a result of search, we can say that there is a logical of networks in time to elect Bogotá as destination. Usually, relatives or acquaintances, whose migrated before - because of the violence or economic reasons- or there is a previous experience housing in Bogotá. These links are essential in processes of adaptation to city. With the coexistence in the city, displaced persons will meet neighbors, coworkers, employees of NGOs and institutions of the state, which will be adding to the range of their relationships. However, violence, fear and distrust are some factors that influence the incorporation of new ties and the preservation of ancient, affecting the dynamics and the configuration of networks
Keywords: Migração; Redes sociais; Suporte social; Conflito armado Colômbia; Deslocamento interno Bogotá; Migration; Forced migration; Social networks; Social support; Armed conflict-Colombia; Internal displacement-Bogotá; CIENCIAS HUMANAS